Falling Insulin Prices — What Just Happened? - Dafny, Leemore S. (The New England journal of medicine, 2023)
Falling Insulin Prices — What Just Happened?Recently, more than 100 years after insulin was developed, manufacturers announced price reductions for insulin products. Pressure to reduce prices had long been building, so why would they act now?